ANALYSIS OF SOCIAL, MORAL, AND EDUCATIONAL VALUES IN POLLYANNA NOVEL BY ELEANOR H. PORTER - Natalina Simanjuntak; Rina Octavia Simarmata; Sahat Taruli Siahaan (Sean Institute, 2023)
This study aims to determine (1) the social, moral, and educational values contained in the novel